Long-term vaccine efficacy of a 2-dose varicella vaccine in China from 2011 to 2021: A retrospective observational study - Shu, Mingming; Zhang, Dandan; Ma, Rui; Yang, Tianchi; Pan, Xingqiang (Frontiers in Public Health, 2022)
Objective: A 2-dose varicella vaccine immunization strategy has been implemented in many cities in China, but there is few evidence on a long-term evaluation of the efficacy of the 2-dose varicella vaccine from China. This study aims to assess the long-term vaccine efficacy of the two doses varicella vaccine and analysis of its influencing factors. Methods: A retrospective study was carried out in 837,144 children born between 2011 and 2017 in Ningbo, easten China. The logistic regression was performed to estimate varicella vaccine effectiveness (VE). Results: The overall VE of 2 doses of varicella vaccine compared without the vaccine was 90.31% (89.24%-91.26%), and the overall incremental VE of 2 doses of varicella vaccine compared to the 1-dose was 64.71% (59.92%-68.93%). Moreover, the varicella vaccination age of the second dose and the interval between 2 doses were both associated with VE. The VE compared to that without the vaccine in children vaccinated at < 4 years was 91.22% (95%CI: 90.16%-92.17%) which was higher than in children vaccinated at ≥ 4 years (VE: 86.79%; 95%CI:84.52-88.73). And the effectiveness of the vaccine was 93.60% (95%CI:92.19%-94.75%) in children with the interval of the 2 doses ≤24 months significantly higher than in children with the interval of ≥36 months (VE: 85.62%, 95%CI:82.89%-87.91%). Conclusions: This study provides evidence for long-term VE of the 2-dose varicella vaccine and the better age for 2-dose vaccination and the interval between 2 doses of the vaccine in China.